Writing a new story on crumpled paper: the embodied experience of being and becoming a sustainability professional - Aguiar, Ana Carolina Pires de (2022)
The objective of this study is to understand, under a phenomenological approach, the embodied lived experience of sustainability professionals in relation to their sense of self, relationship to others, nature and work. While the sustainable development agenda has become more legitimate in organizations, engaging with social and environmental issues still challenges dominant discourses of shareholder value and economic growth. In a deeper level, sustainability calls us to an ontological shift - from an anthropocentric to an ecocentric paradigm - that overcomes human-nature dualism and the prevalence of technical knowledge that tends to remove the knower from the process of knowing as if people were detached, disembodied, and neutral observers of a given reality. Few studies related to sustainability professionals adopt an epistemological approach coherent with such challenges. Building on this opportunity, my study uses Merleau-Ponty's Phenomenology of Perception as philosophical positioning and Interpretative Phenomenological Analysis (IPA) as research method, with interviews as data collection. Findings from seventeen interviewees with sustainability professionals from different sectors illustrate how they go through experiences as embodied-selves-with-others-in-the-world in ambiguous ways. As a relational and ever-emerging challenge, sustainability allows direct contact to different people, places and realities, which works as enablers for an ontological shift. Embodiment enlarges professionals´ perception in relation to themselves, others and nature as body cues provide wake up calls influencing new perspectives, meanings and actions. Finally, the experience of being and becoming a sustainability professional can be understood as a matter of presence where ambiguous movements of past-future, body-mind, self-others-nature meet in the challenge of metaphorically writing a new story on crumpled paper.